Everyday enterprise architecture : sense-making, strategy, structures, and solutions - Graves, Tom, 1951- (Apress, 2023)
Discover what needs to happen in enterprise-architecture practice--and not just its outcomes, but also the activities from which those outcomes would arise. This book reveals how business and enterprise architects can deliver fast solutions to an always-on-the-go business world. To begin, you'll review a new technique called "context-space mapping," which provides a structured method for sense-making across the entire context of an enterprise. Throughout the book, you'll concentrate on the routine practices that underpin each of the architecture disciplines. Working step-by-step through a real 10-day architecture project, this book explores the activities that underpin the strategy, structures and solutions in the real-time turmoil of an enterprise architect's everyday work. You'll explore how and why and when the various documents, artefacts and items of 'theory-stuff' come into the practice - all those mainstream methods, frameworks, models, metamodels and other information sources. In the end, Everyday Enterprise Architecture will help you develop the skills, judgment, and awareness to keep enhancing the value of your architectural projects. What You'll Learn Work on architectures at "business-speed" Adapt architectures for different tasks Gather, use, and manage architectural information Who This Book Is For Enterprise and business architects.